Impact of post-surgical freezing delay on brain tumor metabolomics - Mock, Andreas; Rapp, Carmen; Warta, Rolf; Abdollahi, Amir; Jäger, Dirk; Sakowitz, Oliver; Brors, Benedikt; Deimling, Andreas von; Jungk, Christine; Unterberg, Andreas; Herold-Mende, Christel (Metabolomics, 2019)
Introduction: Translational cancer research has seen an increasing interest in metabolomic profiling to decipher tumor phenotypes. However, the impact of post-surgical freezing delays on mass spectrometric metabolomic measurements of the cancer tissue remains elusive. Objectives: To evaluate the impact of post-surgical freezing delays on cancer tissue metabolomics and to investigate changes per metabolite and per metabolic pathway. Methods: We performed untargeted metabolomics on three cortically located and bulk-resected glioblastoma tissues that were sequentially frozen as duplicates at up to six different time delays (0-180 min, 34 samples). Results: Statistical modelling revealed that 10% of the metabolome (59 of 597 metabolites) changed significantly after a 3 h delay. While carbohydrates and energy metabolites decreased, peptides and lipids increased. After a 2 h delay, these metabolites had changed by as much as 50-100%. We present the first list of metabolites in glioblastoma tissues that are sensitive to post-surgical freezing delays and offer the opportunity to define individualized fold change thresholds for future comparative metabolomic studies. Conclusion: More researchers should take these pre-analytical factors into consideration when analyzing metabolomic data. We present a strategy for how to work with metabolites that are sensitive to freezing delays.
Gesehen am 16.09.2019